PROGRAM PENGEMBANGAN KEWIRAUSAHAAN BERBASIS TEKNOLOGI DI IIB DARMAJAYA LAMPUNG - Melda Agarina; Susanti Susanti; Hendra Kurniawan; Yusminar Yusminar; M Yusendra; Stefanus Rumangkit (Politeknik Negeri Sriwijaya, 2020)
Technology-based startups, or tech startups, are growing exponentially, bringing various kinds of business models to market and becoming key industry players. In Indonesia, over 1,500 tech startups have emerged, with some of them able to make their mark and gain a strong customer base only in a few years. IIB Darmajaya, with its entrepreneurial vision “Be Bold, Be Vibrant and Be Technopreneurship”, has been relentlessly working hard to help its students transition into tech businesses. However, the success rate has not been quite impressive due to their lack of experience in business management, meager access to capital and market, and minimum guidance and mentoring from business incubators. Our current program will implement Darmajaya’s Six Success Stages of Technopreneurship Incubation in order to select twenty candidates for technology-based entrepreneurship as well as five tenants, who will be directed in managing their business. The entire activities will be run under cooperation with multiple parties, including the university’s entrepreneurship lecturers and student affairs department, the Department of Industry and Commerce, and the existing cooperatives and microbusinesses. This partnership is expected to increase tenants’ survivability and refine their exit strategies, so that they are able to build strong and durable businesses.